Physico-chemical Properties of Fresh and Stored Meat as Influenced by Dietary Supplementation of Soy Acid Oil and Crude Soy Lecithin Alone or in Combination in Vencobb Broiler Chicken - Danipreetha, S.; Dubey, Meenu; Tiwari, S. P.; Dutta, G. K.; Pandey, Abhishek (Indian Journal of Animal Nutrition, 2017)
Day-old Vencobb broiler chicks (n= 288) were allocated to 6 dietary groups with 4 replicates of 12 birds in each. T1 was control, T2 and T3 contained 3% crude soy lecithin (CSL) and 2.5% soy acid oil (SAO) respectively, T4 to T6 contained both CSL and SAO (level 3%) in different combinations (75: 25, 50: 50 and 25:75,respectively). The diets were isocaloric and isonitrogenous. The mean pH value of fresh meat samples in control was higher (P<0.05) as compared to groups T4, T5 and T6. The pH value was higher (P<0.05) in fresh meat as compared to deep freeze stored meat irrespective of treatment. The addition of SAO and CSL alone or in combination did not influence the extract release volume (ERV) values in fresh and stored meat samples. Storage of meat resulted in reduction (P<0.01) in the water holding capacity of meat in all the treatments. Storage of meat led to significant (P<0.01) increase in the malonaldehyde concentration in meat. There was significant increase in the tyrosine value of stored meat as compared to fresh meat in all the treatments. It was concluded that addition of SAO and CSL alone or in combination did not influence the pH and ERV of fresh as well as stored meat samples. Soy acid oil alone or in higher proportion alongwith crude soy lecithin decreased the water holding capacity of fresh meat and storage of meat resulted in increased tyrosine and TBA value.